2005
DOI: 10.1111/j.1745-493x.2005.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ailing Healthcare Supply Chain: A Prescription for Change

Abstract: SUMMARY Despite well‐documented evidence of significant competitive advantage and cost reduction resulting from supply chain management (SCM) practices, the healthcare industry has been extremely slow to embrace these practices. This article, through literature review and case studies within the healthcare industry supply chain, explores the barriers to implementation of SCM practices. These barriers include: lack of executive support; misaligned or conflicting incentives; need for data collection and performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 6 publications
1
141
0
2
Order By: Relevance
“…In this sense, the supply chain structure has a two-fold effect, comprising both cost reduction [9,10] and generation of added value [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the supply chain structure has a two-fold effect, comprising both cost reduction [9,10] and generation of added value [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the physical flow of supplies within hospitals, there are large quantities of time-sensitive data connected to the material services (Singh 2006 ), much of which are indicators of hospital demand; and, numerous stakeholders such as manufacturers, distributors, GPs, materials management professionals, doctors and other clinicians (McKone-Sweet et al 2005). The large number of stakeholders and vast amounts of data generated by each raises issues regarding the sustainability of the supply chain operation.…”
Section: Hospital Supply Mechanismsmentioning
confidence: 99%
“…Research into demand variance within healthcare has found that hospital orders exhibit considerable variability (Shapiro and Byrnes 1992), affecting supplier's abilities to respond, in some cases impacting on the hospital's ability to deliver quality patient care and treatment (McKone-Sweet et al 2005;Costantino et al 2010). Unclear inventory demand between wards and central procurement / suppliers can create a 'bullwhip' effect ( Figure 1), resulting in a lack of coordination in ordering policies at points throughout the supply chain, creating an increasing demand variance propagating up the chain (Christopher 2011).…”
Section: Healthcare Supply Chain Structurementioning
confidence: 99%
“…In addition to this, the nature of medical developments within the healthcare supply chain, such as: constantly evolving technologies and short product life cycles; a lack of standardised nomenclature / coding for products due to participation from numerous suppliers worldwide; and a lack of capital to build sophisticated information and communications technology infrastructure are significant barriers to the implementation of more efficient SCM solutions (McKone-Sweet et al 2005). …”
Section: Characteristics Of Hospital Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation